Taxonomic revision of Justicia sect. Harnieria (Acanthaceae) from the Philippines - Tong, Yi; Deng, Yunfei (Phytotaxa, 2021)
Justicia sect. Harnieria is revised from the Philippines for the first time. Seven species are recognized. Two new combinations (J. aspera and J. ramosii) and a replacement name (J. sulitii) are proposed. An identification key to the species is provided. The lectotype is designated for the name Justicia loheri. The description, line drawings and distribution maps are also provided for each species excluding J. aspera.